PENGARUH PEMIKIRAN PENDIDIKAN QASIM AMIN PADA PROPONEN FEMININ - Khoirul Mudawinun Nisa’ (Ta`Limuna: Jurnal Pendidikan Islam, 2014)
The result of social construction that distinguishes human based on gender discriminates female in deserving the education. Against the Egyptian tradition that isolated women and treated them such as slaves, Qasim Amin (1863-1908) came forth featuring the ideas of woman liberty and attempting their advancement through his two both phenomenal books, Tahrir Mar’ah and al-Mar’ah al-Jadidah.  But, the voice to free women from the shackles of tradition, in the eyes of contemporary female education world is irrelevant, regarding women who are easily to deserve their education. The relevant agenda should be proposed today is to empower woman and not to liberate women. This article denotes the influences of Qasim Amin’s educational thought to the feminine proponent and questions its relevance toward female education.